Cytotoxicity effect of honey, bee pollen, and propolis from seven stingless bees in some cancer cell lines - Enos Tangke Arung (Elsevier, 2021)
Our effort to find new material for anti cancer from natural resources leads us to focus on stingless bee products such as honey, bee pollen, and propolis. The products were from seven stingless bees named Homotrigona fimbriata, Heterotrigona itama, Heterotrigona bakeri, Tetragonula sarawakensis, Tetragonula testaceitarsis, Tetragonula fuscobalteata, Tetragonula laeviceps. The stingless bee products were evaluated for their cytotoxicity effect on MCF-7, HeLa and Caco-2 cancer cell lines. This is the first time to be reported that the honey, ethanol extracts of bee pollen and propolis of H. fimbriata displayed more potent cytotoxicity than other stingless bee products. By chromatography and biological activity-guided fractionation, ethanol extract of propolis from H. fimbriata was fractionated and isolated its active compound named mangiferonic acid. Mangiferonic acid showed a cytotoxicity effect with IC50 values 96.76 µM in MCF-7, >110.04 µM in HeLa, and > 110.04 µM in Caco-2, respectively. These results exhibited the potential of ethanol extracts from propolis of H. fimbriata to be further developed for drug and experiments to verify the function are essential.